Buried secrets - Finder, Joseph (Finder, Joseph. Nick Heller series., 2011)
Nick Heller comes to the aid of family friend Marshall Marcus, whose daughter Alexandra, has been kidnapped and held captive in an underground crypt; but as Nick digs deeper into Marshall's life, he finds that his criminal activities have left behind scores of enemies that reach to the highest levels of government.